Intention to adopt blockchain technology for collaborative business processes by academic libraries in South Africa - Lengoatha, Lebohang (Department of Information Systems, 2023)
Globalisation has compelled academic institutions to leverage digital innovations that present new capabilities and novel opportunities because of the stiff competition and movement restrictions during pandemic such as COVID-19, in their operating environments. In this digital era, academic libraries, like any other institution are compelled to re-think of their ways of providing information services to remain relevant to their communities as there are various other sources of information which attract users' attention. Growing demand of information services, declining budgets, rapidly changing world around academic libraries and increase in prices are common challenges experienced by the university libraries globally, which are mostly too complex and large for the institutions to handle on their own. These challenges led to the consortia formation both in developing and developed countries for collective acquisition and sharing of resources. Collaborative technologies should, therefore, be adopted to integrate internal systems for seamless information exchange between different institutions and eliminate duplication of efforts. However, it becomes a challenge to integrate these systems across independent institutions because of lack of trust between the involved parties, in terms of who will control the collaborative business processes. For collaborative processes which are in place, academic libraries still depend on a third party to facilitate their collaborative activities, and consequently incur costs for coordination of such processes. Blockchain represents one of the disruptive technologies with potential to streamline the collaborative activities across academic libraries with high level of trust without the third party intermediation. Although, blockchain technology has caught the attention of different industries, it is still at an infancy stage and yet to find its traction in various business processes. The aim of this study was to investigate the intention to adopt blockchain technology for collaborative business processes by academic libraries in South Africa. The study was anchored in the Technology Adoption in Supply Chain (TASC) model which has been adapted to answer the research questions formulated. Quantitative research approach was adopted, using survey questionnaire. From the questionnaires sent to 23 South African academic libraries which are members of the regional consortia, only 95 usable responses have been collected and analysed using SPSS version 26. Potential applications of blockchain technology were found to be in distributed metadata sharing, a credentialing system, and a library network connection to form Inter-Planetary File System (IPFS). However, participants are uncertain of the intention to adoption blockchain by their academic libraries. Looking at the results of the descriptive analysis, it is evident that academic library workers are positive about relative advantage, compatibility, IT readiness, and interorganisational trust of blockchain technology in their profession. They are not aware and/or have mixed perceptions of the technology complexity, cost, management support, industry support, customer pressure, and security/privacy concern of blockchain technology. This warrants the need to impart knowledge about the technology and its potential value to their profession. Among the adoption factors included in the model, only customer pressure (CP) was found to be significant in influencing the intention to adopt blockchain, while relative advantage (RA), compatibility (CT), complexity (CX), perceived cost (PC), organisational size (OS), management support (MS), IT readiness (IR), industry support (IS), security concern (SC) and inter-organisation trust (TR) were insignificant. This research contributes to the limited empirical research literature in the blockchain technology adoption intention in academic libraries, while also provides the insights for practitioners in the technology adoption decision making, and technology vendors, in the context of developing countries.